Les fonds chalutables de la region nord de la Tunisie. 2. Potentialities de la peche, ecologie et repartition bathymetrique des poissons - AZOUZ, Abderrazak (INSTM Bulletin : Marine and Freshwater Sciences, 1974)
The sea bottom along the Tunisian coast has been surveyed from the trawlable circalittoral depth (50 m) to the bathyal (600 m) with a view to establishing a precise fishing chart and also to understand the ecology and associations of the ichthyological fauna.